Ovarian cancer detection combining an innovative catheter for uterine and tubal lavage with ultra-sensitive TP53 sequencing. (1st November 2019) - Speiser, P; Maritschnegg, E; Heitz, F; Pecha, N; Bouda, J; Trillsch, F; Grimm, C; Vanderstichele, A; Agreiter, C; Harter, P; Obermayr, E; Vergote, I; et al.
Abstract : Introduction/Background: Poor survival of high-grade serous pelvic cancer (HGSC) is caused by a lack of effective screening measures. Uterine and tubal lavage (UtL) is the sampling technique for HGSC detection with the highest sensitivity ever reported. We combined UtL with the highest accuracy sequencing technology for TP53 mutations, Duplex Sequencing (DS) in order to develop a test potentially feasible for HGSC screening. Methodology: In study I, the clinical feasibility of UtL using a new catheter was examined in 93 patients undergoing surgery for suspected HGSC. In study II, pain at UtL under local anesthesia was evaluated in 22 healthy women. In Study III, uterine lavages from 10 HGSC patients and 11 controls were subjected to DS to identify TP53 mutations. Results: In study I, UtL was performed successfully in 92 (98.9%) of 93 cases by 16 gynecologists. In 84.8% of patients no cervical dilatation was required. For benign conditions, the need for dilatation was associated with menopause status (OR, 4.929; 95% CI, 1.439–16.884; P=0.016). In study II, pain during UtL was rated with a median VAS score of 1.6. During 4 weeks after UtL, no serious complications occurred. UtL took 6.5 minutes on average. The amount of extracted DNA was above the lower limit for sensitive, deep-sequencing mutation analysis in all cases. In study III, in 80% of all HGSC tumor-derived TP53 mutations in UtL samples were detected by DS. However, we detected low frequency TP53 mutations in nearly all samples tested. Mutations increased with age and shared the selection traits of clonal TP53 mutations commonly found in human tumors. However, tumor-derived TP53 mutations were present at frequencies at least 10-fold higher than background mutations. Conclusion: The UtL concept fulfils all prerequisites to be used in a potential screening setting. Interpretation of DS results needs to consider TP53 biologic background mutations. Disclosure: Philipp Harter COI: Honoraria: Astra Zeneca, Roche, Sotio, Tesaro, Stryker, ASCO, Zai Lab, MSD; Advisory Board: Astra Zeneca, Roche, Tesaro, Lilly, Clovis, Immunogen, MSD/Merck; Research funding (Inst): Astra Zeneca, Roche, GSK, Boehringer Ingelheim, Medac, DFG, European Union, DKH, Tesaro, Genmab Rosana Risques COI: RAR shares equity in NanoString Technologies Inc. and is the principal investigator on an NIH SBIR subcontract research agreement with TwinStrand Biosciences Inc. Florian Heitz COI: Honoraria: AstraZeneca, Roche, Tesaro, Clovis; Advisory Board: Astra Zeneca, Roche, Tesaro, Clovis Christoph Grimm COI: Consultant: AstraZeneca, Celgene, MSD, PharmaMar, Roche, Tesaro, Vifor Pharma Speaker: Amgen, AstraZeneca, MSD, PharmaMar, Roche, Tesaro Direct research funding: Meda Pharma, Roche Diagnostics Ignace Vergote COI: CONSULTING = ADVISORY BOARD: Advaxis, Inc., Eisai Inc., MSD Belgium, Roche NV, Genmab, F. Hoffmann-La Roche Ltd, Pharmamar, Millennium Pharmaceuticals, Clovis Oncology Inc., AstraZeneca NV, Tesaro, Oncoinvent AS, Immunogen Inc, Sotio CONTRACTED RESEARCH (via KULeuven): Oncoinvent AS, Genmab GRANT = CORPORATE SPONSORED RESEARCH: Amgen, Roche, Stichting tegen Kanker Accomodations, travel Fabian Trillsch COI:Consultant: AstraZeneca, Roche, Tesaro Speaker/Travel Expenses: AstraZeneca, Medac, PharmaMar, Roche, Tesaro Paul Speisr: Share Holder OVARTEC GmbH.